2014
DOI: 10.3389/fpls.2014.00276
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the study of prolamin storage protein organization and function

Abstract: Prolamin storage proteins are the main repository for nitrogen in the endosperm of cereal seeds. These stable proteins accumulate at massive levels due to the high level expression from extensively duplicated genes in endoreduplicated cells. Such abundant accumulation is achieved through efficient packaging in endoplasmic reticulum localized protein bodies in a process that is not completely understood. Prolamins are also a key determinant of hard kernel texture in the mature seed; an essential characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(116 citation statements)
references
References 60 publications
3
111
0
2
Order By: Relevance
“…In this study, however, globulin-less mutation was unique to induce partial degradation of glutelin rather than compensation. Although compositional change of protein bodies induced by RNAi was demonstrated to result in irregular structure of PB in maize (Holding, 2014), wheat (Gil-Humanes et al, 2011), and rice (Kawakatsu et al, 2010;Nagamine et al, 2011), partial degradation has not ever been reported. Considering our results together with the fact that globulin accumulates on the surface of PB-II (Krishnan et al, 1992;Kumamaru et al, 2010) and its absence results in structurally deformed PB-II (Ashida et al, 2011), globulin protects glutelins from proteinase digestion and thereby facilitates stable glutelin accumulation.…”
Section: Compensation and Degradation In Glutelin And Globulin Mutantsmentioning
confidence: 98%
“…In this study, however, globulin-less mutation was unique to induce partial degradation of glutelin rather than compensation. Although compositional change of protein bodies induced by RNAi was demonstrated to result in irregular structure of PB in maize (Holding, 2014), wheat (Gil-Humanes et al, 2011), and rice (Kawakatsu et al, 2010;Nagamine et al, 2011), partial degradation has not ever been reported. Considering our results together with the fact that globulin accumulates on the surface of PB-II (Krishnan et al, 1992;Kumamaru et al, 2010) and its absence results in structurally deformed PB-II (Ashida et al, 2011), globulin protects glutelins from proteinase digestion and thereby facilitates stable glutelin accumulation.…”
Section: Compensation and Degradation In Glutelin And Globulin Mutantsmentioning
confidence: 98%
“…It seems that developing maize seeds possess compensatory mechanisms that sense protein content when zein synthesis is interrupted, leading to translation of other mRNAs instead of zein mRNAs. Combining deletion mutagenesis with current methods in genome and transcriptome profiling can make it possible to reveal alteration in amino acid composition (Holding 2014). RNA interference based down regulation of 22kD RNAi lines is reported to cause opaque phenotype more profoundly as compared to 19kD component.…”
Section: Genetic Basismentioning
confidence: 99%
“…Zein is primarily present as protein bodies in endosperm cells and can be extracted and separated with various technologies. 6,7 According to solubility and sequence similarity, zein can be further divided into α-, β-, γ-, and δ-zeins. Among these, α-zein accounts for the largest fraction (approximately 80%) of the total zein mass.…”
Section: Introductionmentioning
confidence: 99%